The Societal Role of Youth and Women in Global Conservation of the Environment for Sustainability (Impact: Journal of Transformation, 2022)
An overview of the global environmental condition is necessary for understanding variations of its quality around us. This is desk research aimed at understanding the role played by youth and women in local community conservation of the environment in support of marine life and life on earth. The environmental challenges the world continues to face are the Earth’s triple planetary crisis, such as nature and diversity loss, climate change, and pollution. Biodiversity and ecosystem service loss is as a result of land degradation that is happening rapidly over the world. Degradation is caused by human activities and practices causing climate change, which is a global problem. Society has an obligation to mitigation of greenhouse emissions. The youth, specifically, have much knowhow through their connectivity globally to help conserve the environment through institutionalized and policy-making bodies. By using technology and global sharing of information on climate change and its impacts by the youth, members of local communities can adopt indigenous solutions to reversing trends through sustainable practices in achieving socioeconomic, cultural and environmental benefits. Thus, the protection of the environment begins with local-level initiatives through strengthening local bodies and ensuring that the youth and women take center stage in the preservation of the environment since they have acquired academic knowledge and global interactions through conferences and seminars. The youth understand the challenges of environmental conservation. Since their behavior and attitude can influence their parents and guardians and be the future of our society, they have what it takes to change the world. Therefore, they ought to be given a chance to shape their future since, through their talents, innovation, and education, they understand the environment and its related issues and how to conserve it in their local community.